QATCHEPP: A quality assessment tool for critical health promotion practice - O'Hara, Lily; Taylor, Jane (Frontiers in Public Health, 2023)
Background The origins of health promotion are based in critical practice; however, health promotion practice is still dominated by selective biomedical and behavioral approaches, which are insufficient to reduce health inequities resulting from the inequitable distribution of structural and systemic privilege and power. The Red Lotus Critical Health Promotion Model (RLCHPM), developed to enhance critical practice, includes values and principles that practitioners can use to critically reflect on health promotion practice. Existing quality assessment tools focus primarily on technical aspects of practice rather than the underpinning values and principles. The aim of this project was to develop a quality assessment tool to support critical reflection using the values and principles of critical health promotion. The purpose of the tool is to support the reorientation of health promotion practice toward a more critical approach. Research design We used Critical Systems Heuristics as the theoretical framework to develop the quality assessment tool. First, we refined the values and principles in the RLCHPM, then created critical reflective questions, refined the response categories, and added a scoring system. Results The Quality Assessment Tool for Critical Health Promotion Practice (QATCHEPP) includes 10 values and associated principles. Each value is a critical health promotion concept, and its associated principle provides a description of how the value is enacted in professional practice. QATCHEPP includes a set of three reflective questions for each value and associated principle. For each question, users score the practice as strongly, somewhat, or minimally/not at all reflective of critical health promotion practice. A percentage summary score is generated with 85% or above indicative of strongly critical practice, 50% ≤ 84% is somewhat critical practice, and < 50% minimally or does not reflect critical practice. Conclusion QATCHEPP provides theory-based heuristic support for practitioners to use critical reflection to assess the extent to which practice aligns with critical health promotion. QATCHEPP can be used as part of the Red Lotus Critical Promotion Model or as an independent quality assessment tool to support the orientation of health promotion toward critical practice. This is essential to ensure that health promotion practice contributes to enhancing health equity.